Design and Evaluation of Mobile Application Interface for Expert System of Drug Selection with Local Wisdom using Goal-Directed Design and Heuristic Evaluation Approach - Fajar Novriansyah Yasir; Vicky Bin Djusmin; Ruhamah Ruhamah (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
User interfaces play an essential role in computerized systems, especially expert systems, by facilitating communication between the user and the system. In expert systems designed to replicate experts' decision-making skills, the user interface is critical for receiving information from users and enabling effective interaction with the system. Through this interface, users can enter data and then find a solution to a problem. This research aims to create an interface design for an expert system on medicines with local wisdom. This interface design is needed to create an environment in the form of a system to preserve information about medicines with local wisdom. The approach used in designing the interface is a goal-directed design approach, and a heuristic evaluation approach is used to evaluate the design results. The research results are a high-fidelity mockup with good evaluation ratings, where none of the severity ratings obtained from 25 respondents got a score of more than 1. However, there are two aspects with a score close to 1, namely aspect nine with 0,97 severity ratings score and aspect ten with 0,98. Both focus on the absence of a contact menu that users can contact if they have problems using the application they have created. However, this can be minimized by adding information to the instructions menu section, which is already in the initial design.